Aloe Vera and Shea Butter Gel Lotion: A Formula For Skin Hydration - Cita, Errick Endra; Ka'arayeno, Arie Jefry (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
The overall prevalence of dry skin was found to be 60%. Decreased skin moisture levels can result from various factors, including cold weather, aging, and certain medical conditions. Dry skin is often accompanied by itching and discomfort. The application of moisturizers can improve dry skin and help maintain hydration. The objective of this study was to develop an aloe vera-shea butter lotion gel formulation to retain skin moisture. A descriptive observational design was employed to characterize the properties of the aloe vera-shea butter lotion gel formula. The study included 27 adult participants, all aged over 18 and without a history of allergies. The formulation contained aloe vera leaves, shea butter, vegetable glycerin, xanthan gum, Geogard 221, and rose essential oil. Skin moisture levels were measured using a skin moisture detector. The results showed that the lotion gel had a pH of 5, a homogeneous consistency, a spread ability of 6 cm, a white color, a characteristic aloe vera and rose scent, and a thick, smooth texture. An irritation test revealed that 96.3% of participants experienced no irritation. Additionally, the formulation significantly increased skin moisture, transitioning from dry to moisturized skin. The average percentage increase in skin moisture was 23.25% at 1 minute, 34.96% at 3 minutes, and 34.69% at 5 minutes after application. In conclusion, the aloe vera-shea butter lotion gel formulation effectively enhanced skin moisture levels. This formula can be used as an intervention to address dry skin or moisture depletion in future studies.